Is genetic testing required in a child with an ovarian germ cell tumour? - Nowak, Małgorzata; Pastorczak, Agata; Moczulska, Hanna; Barańska, Dobromiła; Krajewska, Karolina; Sałacińska-Łoś, Elżbieta; Młynarski, Wojciech; Trelińska, Joanna (Pediatria Polska - Polish Journal of Paediatrics, 2019)
In children the most commonly diagnosed ovarian neoplasms are germ cell tumours. The group that shows a particularly high risk of developing gonadal neoplasms are patients with complete gonadal dysgenesis with 46,XY karyotype (CGD, XY; Swyer syndrome). A 12-year-old female patient was diagnosed with a mixed germ cell tumour located in the left ovary. The patient underwent chemotherapy and was provided with medical care at a genetic outpatient clinic. The secondary diagnosis of CGD, 46,XY resulted in the child being qualified for elective right-side gonadectomy. Imaging examinations that preceded the surgical procedure showed a cyst in the right ovary. It was resected together with the tumour, which was identified as undifferentiated pleomorphic sarcoma of giant cell type. The child has been regularly assessed at the oncological outpatient clinic, in the disease remission, for nine months since the second cancer was diagnosed.